CLOSE APPOSITIONAL CONSTRUCTIONS WITH PROPER NAMES - Bielitska, Yevgeniya (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
The article discusses a number of restrictive (close) appositive constructions, compares them with complex proper names in the English language and some Slavic languages. The phenomenon of apposition has attracted considerable attention within linguistic research. Various approaches have been taken towards the definition of the phenomenon. The author emphasizes that grammar oriented approach to properhood can bring more relevant results to the understanding of proper names. The purpose of the article is to consider linguistic account that could correlate with the proper names analysis. Theoretical background of the paper is based on the tenets of Construction Grammar with its treatment of language as a collection of “form and function pairings”. Special attention is paid to the existence of taxonomic and inheritance links between appositions and complex names. It is argued that close appositions and complex names can be derived from the same underlying schema. It is shown that appositives are to be defined through the phenomenon of quotation which is treated broadly covering not only exact words but extralinguistic matters – events. Thus, it is explained that certain types of close apposition involve quotation of naming and calling events. The analysis of the appositional constructions as a consrtucticon, where the taxonomic and inheritance links are taken into prime attention, the study of the so-called traditional appositional types along with complex names provide a better understanding of the linguistic phenomenon. Specific network architecture of mind (mythological thinking) proves an efficient background for considering a network architecture of appositives with the proper names as their part. As a result grammatical status of proper names appears more obviously connected with the events of naming and calling and their further linguistic behavior – with the quotation of these events.